Stapled versus handsewn methods for colorectal anastomosis surgery: a systematic review of randomized controlled trials - Lustosa, Suzana Angélica da Silva (2002)
CONTEXT: The interest in the results from comparisons between handsewing and stapling in colorectal anastomoses has been reflected in the progressive increase in the number of clinical trials. These studies, however, do not permit conclusions to be drawn, given the lack of statistical power of the samples analyzed. OBJECTIVE: To compare stapling and handsewing in colorectal anastomosis, testing the hypothesis that in colorectal anastomosis the technique of stapling is superior to that of handsewing. DESIGN: A systematic review of randomized controlled trials. SURVEY STRATEGY: Systematic revision of the literature and meta-analysis were used, without restrictions on language, dates or other considerations. The sources of information used were Embase, Lilacs, Medline, Cochrane Controlled Clinical Trials Database, and letters to authors and industrial producers of staples and thread. SELECTION CRITERIA: Studies were included in accordance with randomization criteria. The external validity of the studies was investigated via the characteristics of the participants, the interventions and the variables analyzed. An independent selection of clinical studies focusing on analysis of adult patients attended to on an elective basis was made by two reviewers. DATA COLLECTION AND ANALYSIS: The methodological quality of the studies was assessed by the same reviewers. In addition to the randomization criteria, the masking, treatment intention, losses and exclusions were also analyzed. The meta-analysis was performed using risk difference and weighted average difference, with their respective 95% confidence intervals. The variables studied were mortality, clinical and radiological anastomotic dehiscence, anastomotic stricture, hemorrhage, reoperation, wound infection, time taken to perform the anastomosis and hospital stay. RESULTS: Nine clinical trials were selected. After verifying that it was possible to perform one of the two techniques being compared, 1,233 patients were included, of whom 622 underwent stapling and 611 the handsewing technique. No statistical difference was found between the variables, except for stenosis, which was more frequent in stapling (p < 0.05), and the time taken to perform the anastomosis, which was greater in handsewing (p < 0.05). CONCLUSION: The evidence found was insufficient to demonstrate superiority of the stapling method over handsewing, independent of the level of colorectal anastomosis.